The Effect of Hyperparameters on Faster R-CNN in Face Recognition Systems - Pardede, Jasman; Rijal, Khairul (Ikatan Ahli Informatika Indonesia (IAII), 2025)
Face recognition is one of the main challenges in the development of computer vision technology. This study aims to develop a face recognition system using a Faster R-CNN architecture, optimized through hyperparameter tuning. This research utilizes the